Characterization of a Novel Ni/Activated Carbon-TiO2 Composites and Photocatalystic Mechanism Derived from Organic Dye Decomposition - Zhu, Lei; Cho, Jung-Hwan; Meng, Ze-Da; Choi, Jong-Geun; Park, Chong-Yeon; Ghosh, Trisha; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
The activated carbon (AC) modified with different concentration of nickel chloride to prepare Ni coated activated carbon and it was employed for preparation of Ni/activated carbon-supported TiO2 composite photocatalysts with titanium(IV)-n-butoxide. The characterizations of Ni/activated carbon-supported TiO2 composite photocatalysts were determined by employing BET, SEM, XRD and EDX instruments to analyze the potential factors. The photocatlytic activity was evaluated by degradation of methyl blue and methyl orange dye. The results demonstrated that as-prepared samples could effectively photodegrade methylene blue and methyl orange under UV irradiation. When the optimal nickel dosage was 7.95 wt % its photo-decolorization efficiency was achieved the highest photodegradation rate in this study.